2015
DOI: 10.1016/j.aquaculture.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Taurine: a critical nutrient for future fish feeds

Abstract: Taurine is a sulfonic acid found in high concentrations in animal tissues. In recent years, a number of studies have demonstrated the essentiality of dietary taurine for many commercially relevant species, especially marine teleosts. Consequently, the removal of taurine-rich dietary ingredients such as fishmeal may create a deficiency, of which symptoms include reduced growth and survival, increased susceptibility to diseases, and impaired larval development. These symptoms emphasize the systemic role of tauri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
251
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(271 citation statements)
references
References 197 publications
9
251
0
3
Order By: Relevance
“…According to these studies, the optimum level of taurine supplementation depends on fish species and growth stage of fish. Salze and Davis (2015) have reported that different taurine supplementation levels are needed in different fish species with different growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…According to these studies, the optimum level of taurine supplementation depends on fish species and growth stage of fish. Salze and Davis (2015) have reported that different taurine supplementation levels are needed in different fish species with different growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even though taurine is a non-essential nutrient, its inclusion in diets is often recommended (Salze & Davis, 2015). In fact, many animal feeds do not contain adequate levels of taurine and, as a result of processing methods, taurine content varies considerably (Rhodes, Rossi, Hanson, & Davis, 2011). Consequently, there is a lack of information on the effect of taurine supplementation on soybean meal based diets and its impact on the growth performance and body composition of red snapper.…”
Section: Introductionmentioning
confidence: 99%
“…The role of taurine in fish embryonic and larval development has been reported. Taurine deficiency in fish leads to green liver syndrome (Saize and Davis, 2015). In addition to that, nutrients in FH do not leach due to oils and collagen.…”
Section: 35mentioning
confidence: 99%